Cerium modified mesoporous aluminum as well as preparation method and application thereof

By uniformly dispersing metal cerium in the mesoporous aluminum substrate, a cerium-modified mesoporous aluminum catalyst was prepared, which solved the problem of low efficiency of alumina catalyst in carbon tetrafluoride treatment, and achieved a catalytic effect with high efficiency and long life.

CN119500096AActive Publication Date: 2025-02-25CENT SOUTH UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411414203.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-25
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the prior art, alumina catalysts have problems with low treatment efficiency when treating carbon tetrafluoride, especially after the catalyst is saturated, the decomposition efficiency is greatly reduced, affecting the treatment effect.

Method used

Cerium modified mesoporous aluminum is used as a catalyst to uniformly disperse metal cerium in the mesoporous aluminum substrate to improve the activity and stability of the catalyst. The surface oxygen element of cerium modified mesoporous aluminum accounts for 40% to 50%, and the Ce element accounts for 3 to 10%. The specific surface area of ​​the mesoporous aluminum substrate is ≥100m2/g and the pore size is 2 to 50nm.

Benefits of technology

Cerium-modified mesoporous aluminum has high catalytic activity and long life, which can maintain a high catalytic rate for a long time, significantly reduce the deposition of C and F, avoid catalyst poisoning, and improve the degradation efficiency of carbon tetrafluoride.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500096A_ABST
    Figure CN119500096A_ABST
Patent Text Reader

Abstract

The invention provides cerium modified mesoporous aluminum and a preparation method and application thereof.The cerium modified mesoporous aluminum comprises a mesoporous aluminum substrate and metal cerium, the metal cerium is evenly dispersed in the mesoporous aluminum substrate, the mesoporous aluminum substrate is porous nanoparticles in an amorphous state, and the metal comprises cerium; the mass ratio of the oxygen element on the surface of the cerium modified mesoporous aluminum is 43.61%, the specific surface area of the mesoporous aluminum substrate is larger than or equal to 100 m < 2 > / g, and the aperture of the mesoporous aluminum substrate is 2-50 nm. Based on the increase of the oxygen element on the surface after cerium doping, C in CF4 is promoted to be combined with O to generate gas to escape, C deposition is remarkably reduced, and the problem of catalyst poisoning caused by C and F deposition in the catalytic reaction process in the common technology is effectively relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the application field of a catalyst for decomposing carbon tetrachloride, and in particular to cerium-modified mesoporous aluminum and a preparation method and application thereof. Background Art

[0002] Carbon tetrafluoride is a strong greenhouse gas with a global warming potential (GWP) thousands of times that of carbon dioxide, and its lifespan in the atmosphere is extremely long, up to tens of thousands of years. Therefore, the degradation of carbon tetrafluoride is of great significance for slowing global warming and reducing the greenhouse effect.

[0003] However, carbon tetrafluoride has low reactivity and high stability, and it is difficult to degrade carbon tetrafluoride into harmless or low-harm substances. Since the electronegativity of the fluorine atom (F) in the carbon tetrafluoride molecule is large and the carbon-fluorine bond (CF bond) has a high bond energy, this high bond energy makes the CF bond extremely difficult to break at room temperature and pressure, so carbon tetrafluoride is not easy to react chemically. In addition, the carbon tetrafluoride molecule has a regular tetrahedral spatial structure, and the four fluorine atoms are symmetrically distributed around the carbon atom. This symmetrical structure makes the carbon tetrafluoride molecule highly stable in both physical and chemical properties.

[0004] The existing technology includes carbon tetrafluoride degradation technology using alumina as a catalyst coupled with plasma technology. Although activated alumina is a highly efficient fluoride adsorbent, it still has the disadvantage of low treatment efficiency when treating carbon tetrafluoride. Due to the limitation of adsorption capacity, once alumina reaches a saturated state, the decomposition efficiency will drop significantly, thereby affecting the treatment effect of carbon tetrafluoride.

[0005] Based on the above, it is urgent to study a cerium-modified mesoporous aluminum and its preparation method and application, in order to solve the above problems. Summary of the invention

[0006] The main purpose of the present invention is to provide a cerium-modified mesoporous aluminum and a preparation method and application thereof, aiming to solve the technical problem of low efficiency in degrading carbon tetrafluoride after catalyst saturation in the common technology.

[0007] To achieve the above object, the present invention provides a cerium-modified mesoporous aluminum, comprising a mesoporous aluminum substrate and metal cerium, wherein the metal cerium is uniformly dispersed in the mesoporous aluminum substrate, the mesoporous aluminum substrate is porous nanoparticles in an amorphous state, and the metal comprises cerium;

[0008] The mass proportion of oxygen element on the surface of the cerium-modified mesoporous aluminum is 40% to 50%, the mass proportion of Ce element in the cerium-modified mesoporous aluminum is 3 to 10%, and the specific surface area of ​​the mesoporous aluminum substrate is ≥100m 2 / g, and the pore size of the mesoporous aluminum substrate is 2-50 nm.

[0009] Furthermore, the Ce element accounts for 6% to 8% in the cerium-modified mesoporous aluminum.

[0010] The present invention provides a method for preparing the cerium-modified mesoporous aluminum as described in any one of the above, comprising the steps of:

[0011] Mixing polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture;

[0012] The mixture is sequentially subjected to stirring treatment, drying treatment and calcination treatment to obtain cerium-modified mesoporous aluminum;

[0013] The metal nitrate includes cerium nitrate, and the added amount ratio of the polyether, the nitric acid, the aluminum isopropoxide and the cerium nitrate is 1g:1.5ml:10mmol:0.01-0.05g, wherein the concentration of the nitric acid is 65%.

[0014] Furthermore, the calcination temperature is 500-1000° C., and the calcination time is 1-8 hours.

[0015] Furthermore, in the step of mixing the polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture, the polyether is dissolved in a solvent, and the nitric acid, aluminum isopropoxide and metal nitrate are added under stirring; wherein the mass volume ratio of the polyether to the solvent is 0.01 to 1 g / ml.

[0016] Furthermore, the temperature of the drying treatment is 50 to 80° C., and the duration of the drying treatment is 6 to 12 hours.

[0017] Furthermore, the temperature of the calcination treatment includes 600° C., and the calcination treatment includes: heating the solid particles obtained by the drying treatment to 600° C. at a heating rate of 1-10° C. / min, and calcining for 3-6 hours to obtain the cerium-modified mesoporous aluminum.

[0018] The present invention also provides a use of cerium-modified mesoporous aluminum prepared by any one of the preparation methods described above in carbon tetrafluoride treatment, characterized in that it comprises the steps of:

[0019] The carbon tetrafluoride-containing flue gas to be treated flows through the cerium-modified mesoporous aluminum in a plasma field for decomposition treatment, the flow rate of the carbon tetrafluoride-containing flue gas in the plasma field is 10-50 mL / min, and the concentration of carbon tetrafluoride in the carbon tetrafluoride-containing flue gas is 1%-20%;

[0020] The cerium-modified mesoporous aluminum is placed in the discharge region of the plasma field.

[0021] Furthermore, the input voltage of the plasma reactor forming the low-temperature plasma field is 20-40 kV.

[0022] Furthermore, the flow rate of the carbon tetrafluoride-containing flue gas in the plasma field is 10 to 20 mL / min.

[0023] The beneficial effects achieved by the present invention are:

[0024] The cerium-modified mesoporous aluminum provided by the present invention has high catalytic activity and long service life. The surface oxygen element of the cerium-modified mesoporous aluminum is 40% to 50%. Based on the increase of the surface oxygen element after cerium doping, the C in CF4 is promoted to combine with O to generate gas escape, which significantly reduces C deposition and effectively alleviates the catalyst poisoning problem caused by C and F deposition in the catalytic reaction process in the common technology, so that it can maintain a high catalytic rate for a long time.

[0025] The morphology of the mesoporous aluminum substrate in the cerium-modified mesoporous aluminum of the present invention is optimized. With the doping of cerium element, cerium is evenly dispersed in the mesoporous aluminum substrate, and the specific surface area of ​​the mesoporous aluminum substrate is ≥100m 2 / g, the pore size of the mesoporous aluminum substrate is 2 to 50nm, and the morphology of the mesoporous aluminum substrate is transformed into dispersed porous nanoparticles. With the morphology optimization caused by the modification of the mesoporous aluminum substrate, sufficient active sites are provided for the adsorption and catalysis of carbon tetrafluoride, thereby improving the activity of the catalyst. In addition, with the increase of the specific surface area of ​​the mesoporous aluminum substrate, the dispersion of carbon tetrafluoride particles will also increase, which helps carbon tetrafluoride to be evenly distributed on the catalyst surface, reduce mass transfer resistance, and further improve degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0027] Figure 1 This is a SEM-EDS morphology test diagram of mesoporous aluminum in Analysis Example 1 of the present invention, wherein: Figure 1 (a) is the SEM image of mesoporous aluminum. Figure 1 (b) is the EDS image of mesoporous aluminum;

[0028] Figure 2 This is a morphology detection diagram of cerium-modified mesoporous aluminum using SEM-EDS in Analysis Example 1 of the present invention. Figure 2 (a) is the SEM image of Ce / mesoporous aluminum. Figure 2 (b) is the EDS image of Ce / mesoporous aluminum;

[0029] Figure 3 The XRD patterns of the mesoporous aluminum, cerium-modified mesoporous aluminum and manganese-modified mesoporous aluminum measured in Analysis Example 1 of the present invention;

[0030] Figure 4 TEM image of mesoporous aluminum measured in Analysis Example 1 of the present invention;

[0031] Figure 5 TEM image of cerium-modified mesoporous aluminum measured in Analysis Example 1 of the present invention;

[0032] Figure 6 This is a comparison chart of the decomposition efficiency of CF4 measured by single plasma and plasma field coupled mesoporous aluminum at a flow rate of 20 mL / min in Analysis Example 2 of the present invention;

[0033] Figure 7 This is a comparison chart of the decomposition efficiency of CF4 at a flow rate of 50 mL / min of plasma and plasma field coupled mesoporous aluminum in analysis example 2 of the present invention;

[0034] Figure 8 This is the SEM image of the mesoporous aluminum before and after the reaction in the analysis example 2 of the present invention, wherein: Figure 8 (a) is the SEM image of mesoporous aluminum before reaction. Figure 8 (b) is the SEM image of mesoporous aluminum before reaction;

[0035] Fig. 9 This is a comparison chart of the decomposition efficiency of CF4 using mesoporous aluminum and commercial Al2O3 as catalysts in Analysis Example 3 of the present invention.

[0036] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] It should be noted that, in the absence of conflict, the following embodiments and features in the embodiments can be combined with each other. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention.

[0039] Unless otherwise defined, all technical and scientific terms used in the present invention are consistent with the prior art mastery of the technicians in this technical field and the records of the present invention. Any methods, equipment and materials of the prior art similar to or equivalent to the methods, equipment and materials in the embodiments of the present invention can also be used to implement the present invention. It should be known by those skilled in the art that, as an explanation of the present application document, without affecting the actual understanding of the technical solution of the present application, "Intensity (au)" can be expressed as intensity, "Stress" can be expressed as stress, "Strain" can be expressed as strain, "Grain size" can be expressed as grain size, and "Frequency" can be expressed as frequency.

[0040] When the embodiments give numerical ranges, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. The test methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The materials or reagents required in the following embodiments are commercially available unless otherwise specified.

[0041] In the commonly used technology, during the continuous use of alumina catalysts, the degradation of carbon tetrafluoride produces carbon deposits or other byproducts. These carbon deposits gradually accumulate on the catalyst surface, covering some active sites, resulting in a reduction in the effective surface area of ​​the catalyst and a gradual decrease in the reaction activity. At the same time, the increase in carbon deposits may also cause the catalyst pores to decrease, further affecting the contact between the reactants and the active sites, thereby reducing the catalytic efficiency, and ultimately leading to a significant decrease in the decomposition efficiency of alumina and the deactivation of the alumina catalyst.

[0042] Specifically, referring to the analysis example 3 of the present invention, the decomposition efficiency of the aluminum oxide catalyst drops below 50% at 300 min, which is equivalent to the decomposition efficiency of CF4 by plasma alone, indicating that Al2O3 has been deactivated at this time.

[0043] In order to solve the above problems, the present invention provides a cerium-modified mesoporous aluminum, comprising a mesoporous aluminum substrate and a metal, wherein the metal is uniformly dispersed in the mesoporous aluminum substrate, the mesoporous aluminum substrate is porous nanoparticles in an amorphous state, and the metal comprises cerium;

[0044] The mass proportion of oxygen element on the surface of cerium-modified mesoporous aluminum is 40% to 50%.

[0045] Exemplarily, the mass proportion of oxygen element on the surface of cerium-modified mesoporous aluminum is 43.61%.

[0046] The cerium-modified mesoporous aluminum provided by the present invention has high efficiency in decomposing carbon tetrafluoride. The surface of the cerium-modified mesoporous aluminum is rich in hydroxyl groups, so it has excellent performance when applied to CF4 degradation.

[0047] The cerium-modified mesoporous aluminum provided by the present invention has high catalytic activity and long service life. The surface oxygen element of the cerium-modified mesoporous aluminum is 43.61%. Based on the increase of the surface oxygen element after cerium doping, the C in CF4 is promoted to combine with O to generate gas escape, which significantly reduces C deposition, effectively alleviates the catalyst poisoning problem caused by C and F deposition in the catalytic reaction process in the common technology, and improves the catalytic activity of the cerium-modified mesoporous aluminum, so that it can maintain a high catalytic rate for a long time.

[0048] Specifically, referring to the research in Analysis Example 3 of the present invention, the cerium-modified mesoporous aluminum can reach a stable value of about 60% after 500 minutes, overcoming the catalyst poisoning problem caused by C and F deposition.

[0049] In some embodiments, the specific surface area of ​​the mesoporous aluminum substrate is ≥ 100 m 2 / g, and the pore size of the mesoporous aluminum substrate is 2-50 nm.

[0050] like Figure 2 As shown in (a), with the doping of cerium, cerium is evenly dispersed in the mesoporous aluminum substrate, and the morphology of the mesoporous aluminum substrate is transformed into dispersed porous nanoparticles. With the morphology optimization caused by the modification of the mesoporous aluminum substrate, sufficient active sites are provided for the adsorption and catalysis of carbon tetrafluoride, thereby improving the activity of the catalyst. In addition, with the increase of the specific surface area of ​​the mesoporous aluminum substrate, the dispersion of carbon tetrafluoride particles will also increase, which helps carbon tetrafluoride to be evenly distributed on the catalyst surface, reduce mass transfer resistance, and further improve degradation efficiency.

[0051] The present invention provides a method for preparing cerium-modified mesoporous aluminum, comprising the steps of:

[0052] S1. Mix polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture.

[0053] In other embodiments, the metal nitrate includes cerium nitrate, and the ratio of the added amount of the polyether, the nitric acid, the aluminum isopropoxide and the cerium nitrate is 1 g:1.5 ml:10 mmol:0.01-0.05 g, wherein the concentration of the nitric acid is 65%.

[0054] In the step of mixing the polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain the mixture, the polyether can be dissolved in a solvent, and the nitric acid, aluminum isopropoxide and metal nitrate are added under stirring; wherein the mass volume ratio of the polyether to the solvent is 0.01 to 1 g / ml.

[0055] Exemplarily, the solvent may be ethanol, and the mass volume ratio of the polyether to the ethanol may be 0.05 g / ml.

[0056] Exemplarily, the concentration of nitric acid may be 65%.

[0057] S2. The mixture is stirred, dried and calcined in sequence to obtain cerium-modified mesoporous aluminum.

[0058] The calcination temperature is 500-1000°C and the calcination time is 1-8 hours.

[0059] Exemplarily, the calcination temperature is 600-800° C., and the calcination duration is 1-8 hours.

[0060] Exemplarily, the stirring process may include the steps of: covering the mixture with plastic wrap and stirring at room temperature for about 6 hours.

[0061] The temperature of the drying treatment is 50 to 80° C., and the duration of the drying treatment is 6 to 12 hours.

[0062] In some embodiments, the calcination temperature includes 600° C., and the calcination includes: heating the solid particles obtained by the drying process to 600° C. at a heating rate of 2° C. / min, and calcining for 1 to 8 hours to obtain the cerium-modified mesoporous aluminum.

[0063] The present invention also provides the use of cerium-modified mesoporous aluminum prepared by the above preparation method in carbon tetrafluoride treatment, comprising the steps of:

[0064] The carbon tetrafluoride-containing flue gas to be treated flows through the cerium-modified mesoporous aluminum in the plasma field for decomposition treatment. In some embodiments, the flow rate of the carbon tetrafluoride-containing flue gas in the plasma field can be 10-50 mL / min, and the concentration of carbon tetrafluoride in the carbon tetrafluoride-containing flue gas can be 1%-20%.

[0065] Exemplarily, the flow rate of the carbon tetrafluoride-containing flue gas in the plasma field is 10 to 20 mL / min.

[0066] In some embodiments, the carbon-enriched flue gas does not contain oxygen.

[0067] The mesoporous aluminum may be disposed in a discharge region of the plasma field.

[0068] In some embodiments, the input voltage of the plasma reactor for forming the plasma field may be 20-40 kV.

[0069] For further understanding of the present invention, examples are given below:

[0070] Example 1

[0071] Preparation of Cerium-modified Mesoporous Aluminum by Doping

[0072] 1g of polyether P123 was dissolved in 20mL of ethanol at room temperature, and 1.5mL of 65% nitric acid, 2.04g (10mmol) of aluminum isopropoxide, and 0.434g of cerium nitrate were added under vigorous stirring. Cover the mixture with plastic wrap, stir at room temperature for about 6h, and heat it in a drying oven at 60°C for two days to evaporate the solution. Finally, the obtained solid particles were calcined at 600°C at a heating rate of 2°C / min for 5h to obtain a cerium-modified mesoporous aluminum product - Ce / mesoporous aluminum, wherein the Ce doping concentration of Ce / mesoporous aluminum is 7.84%, that is, the mass fraction of cerium in the surface elements of Ce / mesoporous aluminum is Ce.

[0073] Comparative Example 1

[0074] The other steps in Example 1 remain unchanged, and only 0.025 g of cerium nitrate is replaced with 0.12 mL of manganese nitrate to obtain manganese-doped mesoporous aluminum - Mn / mesoporous aluminum.

[0075] Comparative Example 2

[0076] Preparation of mesoporous aluminum

[0077] Dissolve 1 g of polyether P123 in 20 mL of ethanol at room temperature, add 1.5 mL of 65% nitric acid and 2.04 g (10 mmol) of aluminum isopropoxide while stirring the solution. Cover the mixture with plastic wrap, stir at room temperature for about 6 hours, and then heat it in a drying oven at 60°C for 2 days to evaporate the solution. Finally, calcine the obtained solid particles at 600°C for 5 hours at a heating rate of 2°C / min to obtain mesoporous aluminum.

[0078] Analysis example 1

[0079] The morphology of metal-doped mesoporous aluminum catalysts was determined by SEM-EDS. Figure 1 As shown in the figure, there are a lot of pore structures on the surface of mesoporous aluminum. After the introduction of Ce, its morphology changes to Figure 2 The dispersed nanoparticles shown indicate that metal doping changes the morphology of mesoporous aluminum.

[0080] EDS results show that the O content on the surface of mesoporous aluminum is 26.81% and the Al content is 59.85%.

[0081] After Ce doping, the O element accounts for 43.61% and the Ce element accounts for 7.84% on the surface of Ce / mesoporous aluminum. The results show that Ce doping will change the morphology of mesoporous aluminum and significantly increase the surface oxygen content, which is an important factor in enhancing the catalytic decomposition of CF4 by mesoporous aluminum.

[0082] The physical structure of the catalyst was analyzed by XRD. Figure 3There is no obvious characteristic peak in the XRD spectrum of mesoporous aluminum, indicating that the mesoporous aluminum is in an amorphous state. After doping with Mn and Ce, there is no characteristic peak belonging to aluminum oxide, and no characteristic peak belonging to Mn and Ce oxides, indicating that Mn and Ce do not change the phase structure of mesoporous aluminum, and are evenly dispersed into the mesoporous aluminum substrate.

[0083] The microstructure of the catalyst was analyzed by TEM. Figure 4 As shown in Figure 2, mesoporous aluminum exhibits a typical wormhole-like microstructure with no lattice fringes on the surface, indicating that it has porous and amorphous structural characteristics. After Ce doping, mesoporous aluminum still maintains a wormhole-like microstructure, such as Figure 5 As shown, there is no obvious diffraction ring, which belongs to an amorphous structure. After doping, the material becomes more compact, but still maintains an amorphous state.

[0084] Analysis example 2

[0085] Flue gas with a carbon tetrafluoride concentration of 10% flows through the plasma field coupled plasma field coupled mesoporous aluminum and a single low-temperature plasma field respectively.

[0086] Figure 6 The decomposition efficiency of CF4 by plasma alone and plasma field coupled mesoporous aluminum at a flow rate of 20 mL / min. Figure 7 The decomposition efficiency of CF4 at a flow rate of 50mL / min for plasma alone and plasma field coupled mesoporous aluminum.

[0087] When the flue gas flow rate is 20mL / min, the mesoporous aluminum's CF4 decomposition efficiency reaches a peak of 82% after 100 minutes of reaction, and the mesoporous aluminum is almost deactivated after 500 minutes. When the flue gas flow rate is increased to 50mL / min, the peak of the mesoporous aluminum's CF4 decomposition efficiency can reach 70%, but it will still be deactivated after 500 minutes of reaction.

[0088] Flue gas with a carbon tetrafluoride concentration of 10% flows through the plasma field coupled Mn / mesoporous aluminum, Ce / mesoporous aluminum, and mesoporous aluminum respectively.

[0089] When the flue gas flow rate is 20mL / min, the decomposition efficiency of Mn / mesoporous aluminum on CF4 reaches a peak of 70% after 100min of reaction, and the decomposition efficiency stabilizes at about 60% after 400min of reaction. The decomposition efficiency of Ce / mesoporous aluminum on CF4 reaches a peak of 75% after 110min of reaction, and the decomposition efficiency stabilizes at about 60% after 400min of reaction. Both Mn / mesoporous aluminum and Ce / mesoporous aluminum can maintain a high catalytic efficiency as the reaction time increases. After 400min of reaction, the decomposition efficiency is 10% higher than that of mesoporous aluminum. After the flow rate is increased to 50mL / min, the maximum decomposition efficiency of Mn / mesoporous aluminum and Ce / mesoporous aluminum on CF4 is reduced to 60% and 62%, respectively. After 400min of reaction, the decomposition efficiency of Mn / mesoporous aluminum and Ce / mesoporous aluminum on CF4 is 50%, which is also 10% higher than that of mesoporous aluminum.

[0090] The morphology of the reactive mesoporous aluminum in this analysis example was studied by SEM. Figure 8 As shown in the figure, after the reaction, the pores on the surface of the mesoporous aluminum are corroded, and a large amount of C and F are deposited on the surface of the mesoporous aluminum to form a dense layer; while the morphology of the cerium-modified mesoporous aluminum after the reaction is consistent with that of the cerium-modified mesoporous aluminum before the reaction, and no dense layer appears on the surface. This shows again that cerium doping can slow down the catalytic reaction process C and F precipitation Catalyst poisoning caused by accumulation .

[0091] The experimental results show that Mn and Ce can increase the surface oxygen content, thereby strengthening the oxidation of surface carbon and reducing The poisoning effect of carbon deposition on the catalyst was alleviated, and the oxidation activity of cerium-modified mesoporous aluminum was slightly higher than that of manganese-modified mesoporous aluminum.

[0092] Analysis example 3

[0093] The mesoporous aluminum, commercial Al2O3, and non-catalytic material (blank control group; the figure shows single plasma) prepared in Comparative Example 2 were respectively coupled to a plasma reactor with an input voltage of 25 kV to carry out a comparative experiment on the decomposition of carbon tetrafluoride.

[0094] That is, a 10% carbon tetrafluoride gas was flowed at a flow rate of 10 mL / min through the mesoporous aluminum (shown as mesoporous aluminum), commercial Al2O3 (shown as commercial Al2O3), and a catalytic material-free (blank control group; shown as plasma alone) prepared in Example 1, all of which were in a low-temperature plasma field formed by a plasma reactor with an input voltage of 25 kV, to perform carbon tetrafluoride decomposition treatment, and the decomposition efficiency of the treatment from 0 to 600 min was recorded, as shown in detail. Figure 8 shown.

[0095] according to Fig. 9As shown in the figure, the decomposition efficiency of CF4 by mesoporous aluminum rapidly increased to 85% within the initial 200 minutes, and then slowly increased to a peak of about 99% after about 400 minutes. Under the same conditions, the peak decomposition efficiency of commercial Al2O3 for CF4 was only 74%, and the decomposition efficiency dropped to below 50% at 300 minutes, which was equivalent to the decomposition efficiency of CF4 by plasma alone, indicating that the commercial Al2O3 had been deactivated at this time.

[0096] It can be imagined that with the increase of flue gas flow containing carbon tetrafluoride, such as when the flue gas flow containing carbon tetrafluoride is 20% or 50%, the effective time of commercial Al2O3 will become shorter - with the increase of flue gas flow containing carbon tetrafluoride, the surface of commercial Al2O3 will accumulate carbon deposits, unreacted carbon tetrafluoride or other impurities faster, resulting in increased surface coverage and contamination, thereby reducing the effective active sites of commercial Al2O3, thereby reducing its degradation efficiency and service life.

[0097] The comparison of specific surface area, pore volume and pore size of commercial alumina and mesoporous aluminum is shown in Table 1.

[0098] Table 1 Comparison of specific surface area, pore volume and pore size of catalysts

[0099]

[0100] In summary, the above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A cerium-modified mesoporous aluminum, characterized in that: It includes a mesoporous aluminum substrate and metal cerium, wherein the metal cerium is uniformly dispersed in the mesoporous aluminum substrate, the mesoporous aluminum substrate is porous nanoparticles in an amorphous state, and the metal includes cerium; The mass proportion of oxygen element on the surface of the cerium-modified mesoporous aluminum is 40% to 50%, the mass proportion of Ce element in the cerium-modified mesoporous aluminum is 3 to 10%, and the specific surface area of ​​the mesoporous aluminum substrate is ≥100m 2 / g, and the pore size of the mesoporous aluminum substrate is 2-50 nm.

2. The cerium-modified mesoporous aluminum according to claim 1, characterized in that: The Ce element accounts for 6% to 8% in the cerium-modified mesoporous aluminum.

3. A method for preparing cerium-modified mesoporous aluminum according to any one of claims 1 to 2, characterized in that: Includes steps: Mixing polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture; The mixture is sequentially subjected to stirring treatment, drying treatment and calcination treatment to obtain cerium-modified mesoporous aluminum; The metal nitrate includes cerium nitrate, and the added amount ratio of the polyether, the nitric acid, the aluminum isopropoxide and the cerium nitrate is 1g:1.5ml:10mmol:0.01-0.05g, wherein the concentration of the nitric acid is 65%.

4. The preparation method according to claim 3, characterized in that: The temperature of the calcination treatment is 500-1000° C., and the duration of the calcination treatment is 1-8 hours.

5. The preparation method according to claim 3, characterized in that: In the step of mixing the polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture, the polyether is dissolved in a solvent, and the nitric acid, aluminum isopropoxide and metal nitrate are added under stirring; wherein the mass volume ratio of the polyether to the solvent is 0.01 to 1 g / ml.

6. The preparation method according to claim 4, characterized in that: The temperature of the drying process is 50 to 80° C., and the duration of the drying process is 6 to 12 hours.

7. The preparation method according to claim 6, characterized in that: The temperature of the calcination treatment includes 600° C., and the calcination treatment includes: heating the solid particles obtained by the drying treatment to 600° C. at a heating rate of 1-10° C. / min, and calcining for 3-6 hours to obtain the cerium-modified mesoporous aluminum.

8. Use of cerium-modified mesoporous aluminum prepared by the preparation method according to any one of claims 4 to 7 in carbon tetrafluoride treatment, characterized in that: Includes steps: The carbon tetrafluoride-containing flue gas to be treated flows through the cerium-modified mesoporous aluminum in a plasma field for decomposition treatment, the flow rate of the carbon tetrafluoride-containing flue gas in the plasma field is 10-50 mL / min, and the concentration of carbon tetrafluoride in the carbon tetrafluoride-containing flue gas is 1%-20%; The cerium-modified mesoporous aluminum is placed in the discharge region of the plasma field.

9. The use according to claim 8, characterized in that: The input voltage of the plasma reactor for forming the low-temperature plasma field is 20-40 kV.

10. The use according to claim 8, characterized in that: The flow rate of the carbon tetrafluoride-containing flue gas in the plasma field is 10 to 20 mL / min.

Citation Information

Patent Citations

  • Preparation of pore diameter adjustable mesoporous powdered alumina

    CN101412527A

  • Method for manufacturing a nanoporous alumina based materials with controlled textural and particle size and nanoporous alumina obtained by said method

    CN101878186A

  • Double-component composite aluminum oxide high-thermal stability ordered mesopore material and preparation method thereof

    CN107115864A

  • Mesoporous Metal Doped Cerium Oxide Catalyst

    US20170320042A1

  • Alumina-based compositions and catalysts having high specific surface area

    US5397758A